RESISTENSI MASYARAKAT TERHADAP ELITE BARU PASCA-HELSINKI DI ACEH - Iromi Ilham (Aceh Anthropological Journal, 2018)
The reconcilement of Helsinki became the gateway of the Acehnese transformation which has implicated to the social and political change in Aceh. One other thing is the emergence of former GAM fighter as the new Acehnese elite. The collective trauma of the Aceh community led by "outsiders" before Helsinki treaty years ago made the people of Aceh want to leave hope to the awaknanggroe. However, over the time, as if the history of the past was repeated. People feel the social imbalance that practiced by the new elite who ever once existed as "justice fighters". The failure of reciprocity practiced by the elite as a form of responsibility to the people causes the resistance from society, whether it is in an insinuation or in the open pattern. This is the main study in this paper. Finally, the propaganda Meunyoe keun ie, mandum leuhob.Meunyoeu keun droe teuh, mandum gob which was once massively accepted, has expressed to a new antithesis; Nibak ngeun ie, mangat ngeun leuhob, nibak ngeun droeu teuh, mangat that ngeun gob.